BOHDAN HAVRYLYSHYN: AGENDA FOR THE 21ST CENTURY - Hrabovskyj, Serhiy (Київський національний університет імені Тараса Шевченка, 2017)
The article is devoted to the basic ideas and conceptual developments of the great scientist and public figure Bohdan Havrylyshyn (1926-2016). He was one of the most well-known representatives of the post-war Ukrainian Diaspora in the world. Havrylyshyn was a classic example of what is called self-made-men. Having received a serious education (both engineering and managerial), Havrylyshyn became an adviser to many governments and leading companies in the world, co-founder of the Club of Rome and the World Economic Forum in Davos. The most famous work of Havrylyshyn was a report by the Club of Rome entitled "Towards More Effective Societies. Road Maps To The Future" (published in 1980). It is a concise but thorough analysis of the situation in the then world, a review of the pressing and perspective problems that were at the global and regional levels, and the outline of the medium-term future of the world's leading powers, depending on their chosen scenarios of development. Havrylyshyn said, that his life experience influenced the methodology of "Road Maps To The Future". After all, the author of the report of the Club of Rome certain periods of his life spent in remarkably different from each other in the type of socio-political and economic system of the States, and thus formed an idea of civilization as a system of complementary/competing forms and ways of organizing social life. Havrylyshyn described the world not as a dichotomy of the a priori "good" and "bad", but how the complex patterns of multi-collared ways of life are conveyed, where there may be many "good" variants that are essentially different from each other. Effective societies, in his opinion, can be organized in different ways, and remain effective. Ideas of "Road Maps To The Future" were addressed to the last decades of the twentieth century, but now, for the most part, they remain relevant. In the 21st century Bohdan Havrylyshyn developed them and deepened the critique of the current state of affairs in the world. At the same time, Havrylyshyn considered the main problem almost total "economization" of world outlook and political and economic practice, when attempts are made to bring all social processes - from industry to culture - to one measure, to the expedient financial expediency. The author of the article summarizes these ideas, analyzes their predictive value and justifies critical accusations. Havrylyshyn devoted considerable attention to the problems of asserting Ukraine as an independent state and to find the best scenarios for its development. The article summarizes the views of Havrylyshyn on this issue in a concise form. Keywords: Bohdan Hawrylyshyn, effective societies, the Club of Rome, economic models, development scenarios.

Стаття присвячена основним ідеям і концептуальним розробкам значного вченого та громадського діяча Богдана Гаврилишина (1926-2016). Він був одним із найбільш знаних у світі представників повоєнної української діаспори. Гаврилишин являв собою класичний взірець того, що зветься self-made-men. Одержавши серйозну освіту (як інженерну, так і менеджерську), Гаврилишин став радником багатьох урядів і провідних компаній світу, співзасновником Римського клубу і Світового економічного форуму у Давосі. Найвідомішою працею Гаврилишина стала доповідь Римському клубу під назвою «Дороговкази в майбутнє. До ефективніших суспільств» (опублікована 1980 року). Вона є стислим, але ґрунтовним аналізом ситуації у тодішньому світі, оглядом нагальних і перспективних проблем, які стояли на глобальному і регіональних рівнях, та абрис середньострокового майбутнього провідних держав світу в залежності від обраних ними сценаріїв розвитку. Сам Гаврилишин говорив, що його життєвий досвід вплинув на методологію «Дороговказів у майбутнє». Адже автор доповіді Римському клубу певні періоди свого життя провів у разюче відмінних одна від одної за типом соціально-політичного й економічного ладу країнах, відтак склав собі уявлення про цивілізацію як про систему взаємодоповнюючих/конкуруючих форм і способів організації суспільного буття. Гаврилишин описував світ не як дихотомію апріорі «хорошого» та «поганого», а як помережане складними візерунками різнобарв’я способів життя, де може існувати чимало «хороших» варіантів, істотно відмінних між собою. Ефективні суспільства, на його думку, можуть бути організовані по-різному, та залишатися ефективними. Адресовані останнім декадам ХХ століття ідеї «Дороговказів у майбутнє» і нині у більшості залишаються актуальними. У ХХІ столітті Богдан Гаврилишин розвинув їх і поглибив критику існуючого стану справ у світі. При цьому Гаврилишин головною проблемою вважав ледь не тотальну «економізацію» світогляду й політичної та господарчої практики, коли робляться спроби зведення всіх суспільних процесів – від виробничих до культурних – до одного виміру, до сьогочасної фінансової доцільності. Автор статті стисло описує ці ідеї, аналізує їхню прогностичну цінність та виправданість критичних закидів. Значну увагу Гаврилишин присвячував проблемам ствердження України як незалежної держави та пошуку оптимальних сценаріїв її розвитку. Стаття у стислому вигляді резюмує погляди Гаврилишина на цю проблематику. Ключові слова: Богдан Гаврилишин, ефективні суспільства, Римський клуб, економічні моделі, сценарії розвитку.
БОГДАН ГАВРИЛИШИН: ПОРЯДОК ДЕННИЙ НА ХХІ СТОЛІТТЯ